Treatable traits of chronic airways disease. Issue 1 (January 2018) - Fingleton, James; Hardy, Jo; Beasley, Richard
Abstract : Purpose of review: To describe the rationale on which the treatable traits approach to the management of airways disease is based and the issues that need to be considered for its implementation in clinical practice. Recent findings: In clinical practice, treatable traits can be classified according to both endotypes and phenotypes, broadly grouped within pulmonary, extrapulmonary, environmental and behavioural factors. Specific investigations and treatments are undertaken for each of the traits rather than a 'one size fits all' stepwise approach to pharmacological treatment which currently represents the core of asthma and chronic obstructive pulmonary disease (COPD) guidelines. Although there is strong evidence of the benefit of the treatable traits approach to specific traits in asthma and/or COPD, there is uncertainty regarding the preferred method of implementation, efficacy and cost-effectiveness of multidimensional intervention programmes in clinical practice. It is likely that 'master protocols' for randomized controlled trials will be required to evaluate such multiple interventions in broad populations of patients with airways disease. Summary: Current evidence suggests that the precision medicine approach based on the identification and treatment of treatable traits is preferable to a 'one-size-fits-all' stepwise approach to the treatment of airways disease, although high-quality evidence to guide the practical application of this multidimensional management strategy is now required. Video abstract: http://links.lww.com/COPM/A21 Abstract : Supplemental Digital Content is available in the text